Optimalisasi Pendidikan Nonformal Berbasis Pemberdayaan Perempuan dalam Meningkatkan Kompetensi Usaha, Kemandirian Ekonomi, dan Kesejahteraan Rumah Tangga di Era Transformasi Sosial - Arjang, Arjang; Wahyuningsih, Endang Sri; Kristanti, Desi (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the role of non-formal education based on women’s empowerment in enhancing business competence, economic independence, and household welfare in the era of social transformation. The method used is a literature review with a qualitative approach through descriptive analysis. Data were obtained from Google Scholar and credible websites with a publication range between 1964–2025. Data analysis was conducted using qualitative descriptive analysis, which involved organising information, identifying key themes, comparing findings across studies, and presenting comprehensive interpretations. From 50 initial articles, after a strict selection process based on relevance and quality, 32 articles were used as the main sources. The results indicate that non-formal education contributes significantly to building women’s entrepreneurial skills, increasing financial independence, and strengthening family welfare. The integration of digital literacy, social capital reinforcement, and community support has proven to enhance the effectiveness of non-formal education programs amid the dynamics of social transformation. This study also highlights the relevance of Human Capital Theory, Empowerment Theory, Capability Approach, and Network Society in understanding the relationship between non-formal education and women’s empowerment. The findings provide practical implications for the development of community-based programs, theoretical implications in enriching the literature on women’s empowerment, and policy implications in formulating sustainable socio-economic development strategies.